Comparison study of structural, electrical properties of Copper and Chromium doped Mn-Zn nanoferrites. (2022) - Sharma, Anjana; Jindal, Shilpi; Aggarwal, Nupur; Sanjoli,; Kumar, Gagan
Abstract: Nanotechnology, when this word comes at the top of priority list, it gives deep thought of new advancement in correspondence, clinical science and many other fields. Ferrites nanoparticles have incredible importance attribute to their chemical and actual properties. In present day time we are creating materials for electromagnetic applications and specialized gadgets. The series of copper and chromium doped Mn-Zn ferrite nanoparticles, Mn0.5 Zn0.5 Mx, y Fe2-x O4 (x, y = 0.0, 0.1), was synthesized for the first time in this study utilizing the solution combustion approach. From XRD, the authors have analyzed the single-phase cubic structure. For the undoped and doped MZF the electric properties are also decreased that are used for electromagnetic applications. Due to their outstanding properties like electric, high dielectric constant and low dielectric losses, these materials are used for electromagnetic applications